Cover Picture: Theoretical Investigation of Generator–Collector Microwell Arrays for Improving Electroanalytical Selectivity: Application to Selective Dopamine Detection in the Presence of Ascorbic Acid (ChemPhysChem 9/2013). Issue 9 (14th June 2013) - Oleinick, Alexander; Zhu, Feng; Yan, Jiawei; Mao, Bingwei; Svir , Irina; Amatore, Christian
<x xml:space="preserve">Abstract</x> Generator–collector microwell arrays show excellent performance for selective and sensitive detection of an analyte of interest in the presence of interferents, with redox waves occurring before that of the analyte. Due to the specific geometry of the array and the adequate control of each electrode potential, the analyte signal is increased by redox cycling, while that of the interferent is drastically reduced. The theory and simulations presented on p. 1887 by I. Svir, C. Amatore et al. not only allow proper modeling of the experimental results, but also open up new operating possibilities.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>